Policy Framework for Enhancing Public Service Provision in East Nusa Tenggara, Indonesia: Including Public Communication in Regional Development Management - Noverius H Nggili; Mariano A T Nugraha; Sirilus N M Lelan; Yuan V Elim; Adellia Agusta; Descorina Priscillia Br. Sitompul; Roidah ‘Afro’; Dalmasius Naif; Selsus Terselly Djese; Nur Julqurniati (PT. AVID MEDIA INDONESIA, 2026)
Public communication is a key feature of good regional governance, but one that is often neglected early in the development of decentralized systems. The aim of our research is to find out whether poor communication is a factor for the failure of the development programs to reach the people in East Nusa Tenggara (NTT) Province, Indonesia. The study adopted an explanatory mixed-methods design. A survey was conducted on 210 community members in three districts in NTT namely Kupang, Ende and Flores Timur. Secondary data were obtained from 24 policy papers, government reports, statistical publications and institutional related documents.What we found was a system straining in many ways at once: disjointed institutional structures, chronically underfunded Diskominfo offices, more than 80 local languages that are simply out of reach of standard Indonesian-language messages, and a deep lack of trust between the government and the populace that erodes even genuine attempts at communication. At the same time, a handful of local initiatives – district transparency portals, village-level communication coordinators, and community radio stations – gave a glimpse of what is possible when communication is woven into governance from the outset, rather than just tacked on. The findings informed the design of the Strategic Public Communication Framework (SPCF), a five-pillar model developed for the specific needs of NTT and adaptable to other peripheral administrations in other Asia-Pacific regions.